A new name for an Indian Memecylon, Melastomataceae / P. Lakshminarasimhan; S. P. Mathew - Lakshminarasimhan, P.; Mathew, Sam P. (2007)
A new name, Memecylon balakrishnanii, is proposed for a species of Memecylon described by Balakrishnan & Nair
Keywords: Melastomataceae; Memecylon